Eplontersen for hereditary transthyretin amyloidosis with polyneuropathy - Coelho, Teresa; Marques, Wilson, Jr; Dasgupta, Noel R.; Chao, Chi-Chao; Parman, Yeşim; França, Marcondes Cavalcante, Jr; Guo, Yuh-Cherng; Wixner, Jonas; Ro, Long-Sun; Calandra, Cristian R.; Kowacs, Pedro A.; Berk, John L.; et al. (The journal of the American Medical Association, 2023)
Transthyretin gene silencing is an emerging treatment strategy for hereditary transthyretin (ATTRv) amyloidosis.To evaluate eplontersen, an investigational ligand-conjugated antisense oligonucleotide, in ATTRv polyneuropathy.NEURO-TTRansform was an open-label, single-group, phase 3 trial conducted at 40 sites across 15 countries (December 2019-April 2023) in 168 adults with Coutinho stage 1 or 2 ATTRv polyneuropathy, Neuropathy Impairment Score 10-130, and a documented TTR variant. Patients treated with placebo from NEURO-TTR (NCT01737398; March 2013-November 2017), an inotersen trial with similar eligibility criteria and end points, served as a historical placebo (“placebo”) group.Subcutaneous eplontersen (45 mg every 4 weeks; n = 144); a small reference group received subcutaneous inotersen (300 mg weekly; n = 24); subcutaneous placebo weekly (in NEURO-TTR; n = 60).Primary efficacy end points at week 65/66 were changes from baseline in serum transthyretin concentration, modified Neuropathy Impairment Score +7 (mNIS+7) composite score (scoring range, -22.3 to 346.3; higher scores indicate poorer function), and Norfolk Quality of Life Questionnaire-Diabetic Neuropathy (Norfolk QoL-DN) total score (scoring range, -4 to 136; higher scores indicate poorer quality of life). Analyses of efficacy end points were based on a mixed-effects model with repeated measures adjusted by propensity score weights.Among 144 eplontersen-treated patients (mean age, 53.0 years; 69% male), 136 (94.4%) completed week-66 follow-up; among 60 placebo patients (mean age, 59.5 years; 68% male), 52 (86.7%) completed week-66 follow-up. At week 65, adjusted mean percentage reduction in serum transthyretin was −81.7% with eplontersen and −11.2% with placebo (difference, −70.4% [95% CI, −75.2% to −65.7%]; P < .001). Adjusted mean change from baseline to week 66 was lower (better) with eplontersen vs placebo for mNIS+7 composite score (0.3 vs 25.1; difference, −24.8 [95% CI, −31.0 to −18.6; P < .001) and for Norfolk QoL-DN (−5.5 vs 14.2; difference, −19.7 [95% CI, −25.6 to −13.8]; P < .001). Adverse events by week 66 that led to study drug discontinuation occurred in 6 patients (4%) in the eplontersen group vs 2 (3%) in the placebo group. Through week 66, there were 2 deaths in the eplontersen group consistent with known disease-related sequelae (cardiac arrhythmia; intracerebral hemorrhage); there were no deaths in the placebo group.In patients with ATTRv polyneuropathy, the eplontersen treatment group demonstrated changes consistent with significantly lowered serum transthyretin concentration, less neuropathy impairment, and better quality of life compared with a historical placebo.ClinicalTrials.gov Identifier: NCT04136184; EU Clinical Trials Register: EudraCT 2019-001698-10